Correlation between high‐sensitivity C‐reactive protein and brain gray matter volume in healthy elderly subjects. Issue 10 (22nd March 2012) - Taki, Yasuyuki; Thyreau, Benjamin; Kinomura, Shigeo; Sato, Kazunori; Goto, Ryoi; Wu, Kai; Kakizaki, Masako; Tsuji, Ichiro; Kawashima, Ryuta; Fukuda, Hiroshi
<x xml:space="preserve">Abstract</x> Although elevated serum high‐sensitivity C‐reactive protein (hsCRP) is related to atherosclerosis, brain infarction, and cognitive decline, it has not been clarified whether increased hsCRP is associated with the decline in brain gray matter volume. Therefore, the purpose of this study was to determine the relationship between hsCRP levels and brain regional gray matter volume using brain magnetic resonance imaging (MRI) data from 109 community‐dwelling healthy elderly subjects. Brain MRIs were processed with voxel‐based morphometry using a custom template by applying diffeomorphic anatomical registration using the exponentiated lie algebra (DARTEL) procedure. We found a significant negative correlation between regional gray matter volume of the posterior and lateral aspects of the left temporal cortex and hsCRP level after adjusting for age, gender, and intracranial volume. Our results suggest that subjects who have mild inflammation related to arteriosclerosis have decreased regional gray matter volume in the posterior and lateral aspects of the left temporal cortex. Thus, preventing the progression of arteriosclerosis may be important for preventing a decrease in gray matter volume in healthy elderly subjects. Hum Brain Mapp 34:2418–2424, 2013. © 2012 Wiley Periodicals, Inc.